Prospek Pengembangan Tanaman Tomat (Sollanum lycopesicum L.) di Desa Ladogahar Kecamatan Nita Kabupaten Sikka - Klaudiana Nogolete Keraf (Jurnal Ilmiah Wahana Pendidikan, 2022)
Tomatoes are one of the horticultural commodities that are of high value and are very important in supporting the availability of food and the adequacy of community nutrition. Tomatoes are much loved by people because they taste good, fresh and slightly sour and contain many vitamins. The purpose of this study is to find out the development prospects and what strategies are carried out on tomato plants in Ladogahar Village, Nita District, Sikka Regency. Development prospects are a business that is carried out by taking into account the environmental conditions of the region both internally which includes strengths and weaknesses and externals that include opportunities and threats.. The strategies used are, Stability strategy, Retrenchment strategy, Growth strategy, and Combination strategy. This study uses SWOT analysis. The results of this study show that the prospect of tomato farming development in Ladogahar Village of Nita District of Sikka Regency is in quadrant I position with a value of 5.38 which is the most profitable position for farmers because at this time tomato farming has opportunities and strength so that it can be utilized. The strategy that must be done in this condition is to change the old strategy by replacing the new strategy that utilizes the power and opportunities for the prospects of tomato farming development in the future.